2015
DOI: 10.1177/0009922814563925
|View full text |Cite
|
Sign up to set email alerts
|

Foster Caregivers’ Perspectives on the Medical Challenges of Children Placed in Their Care

Abstract: Foster caregivers receive insufficient information despite the evidence that these children are likely to have complex needs. It is, therefore, necessary for the pediatrician to recognize existing medical problems, identify new medical problems, educate foster caregivers, and communicate with the multidisciplinary team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…This may include facilitating record gathering and record review, providing developmental, educational, and mental healthcare screenings and service referrals, enhanced anticipatory guidance and education for nonparental caregivers, and multidisciplinary collaboration with all stakeholders involved in the care of the child (i.e., child welfare; 65) For researchers, there are several gaps in the literature on children in nonparental care that should be addressed. First, there is currently only one publication of findings from the NSCNC (3,55), and further examination of that cross-sectional data is warranted.…”
Section: The Interplay Between Nonparental Care and Social Antecedentmentioning
confidence: 99%
“…This may include facilitating record gathering and record review, providing developmental, educational, and mental healthcare screenings and service referrals, enhanced anticipatory guidance and education for nonparental caregivers, and multidisciplinary collaboration with all stakeholders involved in the care of the child (i.e., child welfare; 65) For researchers, there are several gaps in the literature on children in nonparental care that should be addressed. First, there is currently only one publication of findings from the NSCNC (3,55), and further examination of that cross-sectional data is warranted.…”
Section: The Interplay Between Nonparental Care and Social Antecedentmentioning
confidence: 99%
“…Health information is often lacking on entry into foster care. 26,27 Foster parents in our study identify obtaining medical records as an area in need of improvement. Because most CMC in our sample entered care because of medical neglect, their history may include multiple "no-show" appointments, resulting in missing records and fragmented care.…”
Section: Qol Datamentioning
confidence: 99%
“…Data describing medical foster families are not robust, but suggest that foster parents often feel inadequately prepared to care for children with medical complexity. Greiner et al (46) reported that foster parents frequently receive fragmented medical information about children placed in their care, such as missing information about medication schedules and prescriptions. They report feeling ill-prepared to navigate the health system and access services, and worry that medical information is withheld when a child is placed in their care to deter their potential refusal.…”
Section: Medical Foster Home Environmentmentioning
confidence: 99%
“…States assign variable authority to foster parents to obtain medical care for a child. Foster parents are typically responsible for determining when a child needs medical attention, and may possess information important to medical decisions (46,49). But unless parental rights are terminated or relinquished, biologic parents are legal custodians and usually retain authority for consenting to medical treatment (49).…”
Section: Shared Medical Decision-making For Foster Childrenmentioning
confidence: 99%